Mit fundacyjny Rzeczypospolitej w Kursie pierwszym Prelekcji Paryskich Adama Mickiewicza - Hoffmann-Piotrowska, Ewa (Colloquia Litteraria, 2017)
The Foundational Myth of the Polish-Lithuanian Commonwealth in Mickiewicz’s Kurs pierwszy from Paris Lectures The article attempts to recreate Mickiewicz’s vision of Polish Medieval history in the context of the history of Slavdom as it is presented by him in the speeches from Kurs pierwszy from the Paris lectures. Invoking particular facts from the first centuries of Polish history and interpreting them in a particularly individual manner – frequently contrary to the traditional historical narrative, Mickiewicz rediscovered the foundational myth of the Commonwealth of the nobles in the history of the Piast and Jagiellonian Poland; furthermore, the whole of the Medieval period served Mickiewicz as a universal political model worthy of translation to the poet’s contemporary period. The modern christianitas state model, which Mickiewicz will later design in his writings from 1830s and 1840s, had its roots precisely in this reinterpreted political history of the Middle Ages. When discussing the past, Mickiewicz first and foremost advocated talking about the present and the future of Poland and Europe. Underscoring the strong relationship between Poland and Rome as well as the ties with Western Christendom – as it used to be done in the Middle Ages – was meant to produce a propagandist image: it attempted to demonstrate that the Byzantine-Orthodox culture could neither serve to unite Slavic peoples nor rejuvenate Europe in any way.